Visual perception and spatial awareness - Behrmann, Marlene (Henry Stewart Talks, 2010)
Selective attention, Unattended information, Spatial cueing of attention, Goal-directed (endogenous) cueing, Stimulus-driven (exogenous) cueing, Spatial attention facilitates detection, Federico Fellini, Anton Raderscheidt, Patients with parietal lesions, Vision and eye movements, Location and duration of fixations, Neglect in visual imagery, Matched control and neglect subjects, Is attention always necessary?, Unconscious processing of neglect information, Priming paradigm, Nature of the task may influence awareness, Perceptual organization in absence of attention, Patients vary in neglect severity, Neural correlates of visual awareness